Mixotrophy in the Antarctic phytoflagellate, Pyramimonas gelidicola (Chlorophyta: Prasinophyta) - Bell, Elanor M.; Laybourn-Parry, J. (2003)
Grazing by the planktonic, phytoflagellate, Pyramimonas gelidicola McFadden (Chlorophyta: Prasinophyta), and heterotrophic nanoflagellates (HNAN) in meromictic, saline Ace Lake in the Vestfold Hills, Eastern Antarctica, was investigated in the austral summers of 1997 and 1999. Up to 47% of the P. gelidicola population ingested fluorescently labelled prey (FLP). Ingestion rates varied with depth. In January 1997 and November 1999, maximum P. gelidicola ingestion rates of 6.95 and 0.79 FLP;cell-1;h-1, respectively, were measured at the chemocline (6-8 m) where a deep chlorophyll maximum composed of phototrophic nanoflagellates (PNAN DCM), predominantly P. gelidicola, persisted all year. During the summers of 1997 and 1999, the grazing P. gelidicola community removed between 0.4 and approximately 16% of in situ bacterial biomass, equivalent to between 4 and >100% of in situ bacterial production. Due to their higher abundance, the community clearance rates of HNAN in Ace Lake generally exceeded those of P. gelidicola but HNAN removed approximately only 3 to 4% of bacterial biomass, equivalent to between 28 and 32% of bacterial production. P. gelidicola growth rates were highest at the PNAN DCM concomitant with the highest ingestion rates. It is estimated that during the summer P. gelidicola can derive up to 30% of their daily carbon requirements from bacterivory at the PNAN DCM. This study confirms mixotrophy as an important strategy by which planktonic organisms can survive in extreme, polar, lacustrine ecosystems.